Kano Model approach for design improvement associated with ergonomics issues in CNC machine design - Sihombing, Haeryip; Halim, Isa; Ab Rahman, Mahmood; Baharudin, Abu Bakar; S.K., Khalid (Penerbit UTeM, 2014)
Application of Computer Numerical Control (CNC) technology in manufacturing industry has been recognized as one of the effective solutions to high productivity, efficiency, and precision. In advancement of CNC machine tool technology development; however, the ergonomic issues related to human-machine design are still less-addressed by scholars. This study was carried out to analyze a CNC machining center based on the operators’ requirements. The functional and dysfunctional questionnaire form developed based on Kano method was applied to determine the operators’ requirements related to technical specifications of the CNC machining center. Another questionnaire form equipped with a diagram of human body parts and ergonomics features was used to acquire information on the CNC machining center design. This study found that there is a significant correlation between the ergonomics problems in the feet towards facilities required for the CNC machining center – an adjustable standing platform. This study concluded that application of Kano model can contribute to operators’ satisfaction in terms of ergonomic design of CNC machining center.